Tarih Edebiyat İlişkisi Bağlamında Bir Devrin Eleştirel Panoraması Abdülhamit Düşerken - Çelik, Yakup (My University, 2009)
Nahit Sırrı Örik Abdülhamit Düşerken romanında, çocukluk yıllarında tanığı olduğu, yakın dönem Türk tarihinin önemli gelişmelerini, merkezinde aşkın bulunduğu olaylar çevresinde kurgulamıştır. Yazar; bir devrin panoraması olarak adlandırabileceğimiz romanında, olaylara, insanların tavırlarını, davranışlarını eleştirel tarzda değerlendiren bir açı ile yaklaşmaktadır. Đttihat ve Terakki’nin henüz ülkeyi yönetecek kadroya sahip bulunmadığı, Abdülhamit’in yalnızlığı, devlet kadrolarının güç ve iktidar savaşı içinde bulunması kurgunun verdiği imkanlar çevresinde vurgulanır. Nahit Sırrı Örik, bir dönemin panoramasını Nimet ile Şefik arasındaki aşkla bütünleştirme yoluna gider. Çünkü, bu aşkın çerçevesine girenler ülkeyi yöneten insanlardır.

In his novel, ‘Abdülhamit Düşerken’, Nahit Sırrı Örik, fictionalizes important developments in late Turkish History, which he witnessed during his childhood, within the scope of events at the center of which stood love. In this novel that we can denominate as the panorama of an era, the author approaches to the event, attitudes of manners and behaviors with a critical style. It is emphasized within the possibilities of the fiction that Đttihat and Terakki still doesn’t have the staff that will rule the country; the loneliness of Abdülhamit and that government staff are in a war of power and status. Nahit Sırrı Örik tries to unify the panorama of an era and the love affair between Nimet and Şefik as within the frame of this love affair are the people who govern the country.
The Crical Panorama of an Era in the Context of the Relation Between History and Literatüre: The Fall of Abdülhamit
Keywords: Örik, Nahid Sırrı, 1895-1960; Yazarlar, Türk; Türk Edebiyatı; Tarihi Roman; II. Abdülhamid, Türk Sultanı, 1842-1918; İttihat ve Terakki Cemiyeti; Authors, Turkish; Turkish Literature; Historical Fiction; Abdülhamid II, Sultan of the Turks, 1842-1918; Committee of Union and Progress